Maintaining the Carceral Echo Chamber: Tensions Within the Anti-Trafficking Movement in Canada - McFadyen, Nicole (Anthropologica, 2022)
The anti-trafficking movement in Canada has grown rapidly since the late 2000s, branding itself as a feminist human rights-based effort to eliminate human trafficking and taken up by the Government of Canada to position itself as a benevolent leader on the international stage. Focusing on the membership of an anti-trafficking coalition in Toronto, Canada, this article explores how the movement creates moral spaces that validate a wide range of anti-trafficking efforts. In unpacking how tensions between members are navigated through the suppression of direct conflict and an ethos of collaboration, it demonstrates how carceral feminist approaches to imagining and eliminating human trafficking continue to remain dominant despite a growth in the efforts of individual members to promote harm reduction and reduce the criminalization of marginalized communities.